PhD chemistry graduate seminar series on medicinal chemistry - Clerigo, Melody (Animo Repository, 2021)
The Chemistry Department College of Science invited the academic community to the PhD Chemistry Graduate Seminar Series on Medicinal Chemistry on Wednesday, September 22, 2021 1800-1940H Title Speaker 6:10-6:50 Virtual Screening of Natural Products Library for M2(S31N) Inhibitor Melody Clerigo (PhD Chemistry Student) 6:50-7:30 Use of peptidomimetics to develop potential SARS-CoV-2 therapeutics Sarah Diane C. Ong (PhD Chemistry Student)